2017
DOI: 10.1016/j.bone.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset hereditary hypophosphatemic rickets with hypercalciuria (HHRH) due to mutation of SLC34A3/NPT2c

Abstract: Objective To identify a genetic basis for markedly reduced bone density and multiple fractures in an adult patient with hypophosphatemia and hypercalciuria. Subjects A 54-year-old Vietnamese man, his unaffected two daughters and wife. Methods We performed biochemical studies and sequenced the SLC34A3 gene using genomic DNA from peripheral blood mononuclear cells. Results Biochemical evaluation of the proband revealed hypophosphatemia with increased renal phosphate wasting, hypercalciuria, low serum parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The group of hypophosphatemic rickets related to a primary kidney pathology includes hereditary hypophosphatemic rickets with hypercalciuria (HHRH, OMIM #241530), related to a mutation with loss of function of the solute carrier family 34 member 3 (SLC34A3) gene (locus 9q34), encoding a protein of the renal NaPi-IIc co-transporter. Clinical symptoms include nephrocalcinosis and nephrolithiasis 27. A mutation of another gene for the sodium-phosphate transporter-solute carrier family 34 member 1 (SLC34A1) (locus 5q35)-in turn follows the autosomal dominant inheritance pattern and is responsible for the occurrence of NPHLOP1(OMIM #612286) syndrome that is characterised by coexistence of nephrolithiasis, osteoporosis and hypophosphatemic rickets.…”
mentioning
confidence: 99%
“…The group of hypophosphatemic rickets related to a primary kidney pathology includes hereditary hypophosphatemic rickets with hypercalciuria (HHRH, OMIM #241530), related to a mutation with loss of function of the solute carrier family 34 member 3 (SLC34A3) gene (locus 9q34), encoding a protein of the renal NaPi-IIc co-transporter. Clinical symptoms include nephrocalcinosis and nephrolithiasis 27. A mutation of another gene for the sodium-phosphate transporter-solute carrier family 34 member 1 (SLC34A1) (locus 5q35)-in turn follows the autosomal dominant inheritance pattern and is responsible for the occurrence of NPHLOP1(OMIM #612286) syndrome that is characterised by coexistence of nephrolithiasis, osteoporosis and hypophosphatemic rickets.…”
mentioning
confidence: 99%
“…Despite the “rickets” designation, late adult onset of HHRH with osteomalacia and recurrent stones was recently reported. 27 A likely heterozygous individual was successfully treated with phosphate, and the authors surmised that heterozygous HHRH may be an overlooked cause of idiopathic low bone density and hypercalciuria.…”
Section: Monogenic Causes Of Stone Diseasementioning
confidence: 99%
“…27,28 Phosphate supplementation is also effective in treating IIH due to SLC34A1 . While further study is needed to determine if forme frustes of HHRH and IIH are prevalent in the general population of stone formers, a trial of phosphate therapy might be considered for those observed to have a mutation and increased 1,25(OH)2D.…”
Section: Monogenic Causes Of Stone Diseasementioning
confidence: 99%
“…As a result, they contribute to diminished phosphate reabsorption in patients with HHRH. 7,26,27 The inheritance pattern of this disorder is autosomal recessive and biallelic mutation is essential for clinical manifestation. However, familial studies revealed that single mutations could also cause some clinical symptoms of HHRH.…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 99%
“…27 Hypercalciuria, which is present in these patients, increases the risk of nephrolithiasis. 24,26 It is interesting to note that Napi-2a cannot compensate for Napi-2c, while both cotransporters act as a modulator of phosphate reabsorption. The reason for this discrepancy is the transient expression of these 2 factors during development.…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 99%